Permanently and retroactively eradicating certain offensive epithets from the scientific names of algae, fungi, and plants: ‘afr-’ is in - Gideon F. Smith; Estrela Figueiredo (Anales del Jardín Botánico de Madrid)
Following publication in 2021 of a proposal to permanently and retroactively eradicate a set of offensive epithets from the scientific nomenclature in use for algae, fungi, and plants, this proposal eventually formed part of the ballot sheet placed before people eligible to cast a preliminary guiding vote (the so-called “mail vote”) to amend the International Code of Nomenclature for algae, fungi, and plants in 2024. In this mail vote the proposal received 74 ‘no’ votes (47%) out of 156 votes cast. This meant that the proposal was not automatically rejected and that it would be put to a vote, following discussion, at the Nomenclature Section of the XXth International Botanical Congress that was held in Madrid, Spain, from 15 to 19 July 2024. We document the process and results of the voting on this proposal during the preliminary guiding vote, as well as during the Nomenclature Section.